Antimosquito property of Petroselinum crispum (Umbellifereae) against the pyrethroid resistant and susceptible strains of Aedes aegypti (Diptera: Culicidae) - J. Intirach (2018)
© 2016, Springer-Verlag Berlin Heidelberg. The increasing and widespread resistance to conventional synthetic insecticides in vector populations has underscored the urgent need to establish alternatives in the mosquito management system. This study was carried out with the aim to investigate the antimosquito property, larvicidal and adulticidal potential, of plant products against both the pyrethroid-susceptible and resistant strains of Aedes aegypti. Seventeen plant products, including essential oils and ethanolic extracts, were obtained by steam distillation and extraction with 95 % ethanol, respectively. Their larvicidal activity was screened, using World Health Organization (WHO) procedures against A. aegypti, Muang Chiang Mai-susceptible (MCM-S) strain. The most effective product was a candidate for investigating larvicidal and adulticidal potential against three laboratory strains of A. aegypti, comprising MCM-S, Pang Mai Dang-resistant (PMD-R), and Upakut-resistant (UPK-R). Potential toxicity of the plant candidate was compared with that of synthetic temephos, permethrin, and deltamethrin. Chemical constituents of the most effective plant product also were analyzed by gas chromatography-mass spectrometry (GC-MS). Results obtained from the preliminary screening revealed the varying larvicidal efficacy of plant-derived products against MCM-S A. aegypti, with mortality ranging from 0 to 100 %. The larvicidal activity of seven effective plant products was found to be dose dependent, with the highest efficacy established from Petroselinum crispum fruit oil, followed by oils of Foeniculum vulgare, Myristica fragrans, Limnophila aromatica, Piper sarmentosum, Curcuma longa, and M. fragrans ethanolic extract (LC50values of 43.22, 44.84, 47.42, 47.94, 49.19, 65.51, and 75.45 ppm, respectively). Essential oil of P. crispum was then investigated further and proved to be a promising larvicide and adulticide against all strains of A. aegypti. The pyrethroid-resistant strains of both PMD-R and UPK-R A. aegypti showed significant resistance to temephos, permethrin, and deltamethrin in either the larval or adult stage. Interestingly, high susceptibility to P. crispum oil was observed in the larvae and adults of MCM-S, which are pyrethroid-susceptible A. aegypti, and comparable to those of the pyrethroid-resistant strains, PMD-R and UPK-R. GC-MS analysis of P. crispum oil demonstrated that 19 compounds, accounting for 98.25 % of the whole oil, were identified, with the main constituents being thymol (42.41 %), p-cymene (27.71 %), and γ-terpinene (20.98 %). In conclusion, the profound larvicidal and adulticidal potential of P. crispum oil promises to form a new larvicide and adulticide against either the pyrethroid-susceptible or resistant strain of A. aegypti. Consequently, P. crispum oil and its constituents can be used or incorporated with other chemicals/measures in integrated mosquito management for controlling A. aegypti, particularly in localities with high levels of pyrethroid and organophosphate resistance.